2015
DOI: 10.1002/2015ja021680
|View full text |Cite
|
Sign up to set email alerts
|

Principal component analysis of Birkeland currents determined by the Active Magnetosphere and Planetary Electrodynamics Response Experiment

Abstract: Principal component analysis is performed on Birkeland or field‐aligned current (FAC) measurements from the Active Magnetosphere and Planetary Electrodynamics Response Experiment. Principal component analysis (PCA) identifies the patterns in the FACs that respond coherently to different aspects of geomagnetic activity. The regions 1 and 2 current system is shown to be the most reproducible feature of the currents, followed by cusp currents associated with magnetic tension forces on newly reconnected field line… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
108
2

Year Published

2017
2017
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(117 citation statements)
references
References 48 publications
7
108
2
Order By: Relevance
“…We attempt to quantify the importance of multiscale FACs with respect to their difference from the current large‐scale understanding and, therefore, choose large‐scale FACs as the baseline (i.e., the R1/R2 system). To define these FACs, we use the fitting method developed by Clausen et al () to derive R1/R2 FACs from AMPERE data and subsequently used prolifically to study the characteristics of large‐scale FACs (Carter et al, ; Coxon et al, , , ; Milan et al, ). We believe the R1/R2 FACs produced from the Clausen et al () method (hereafter C2012) more faithfully represent the distributions than empirical approaches such as Weimar (, ) because they are driven by instantaneous observations (shortcomings of the Weimer, , empirical model for dynamic representation during a geomagnetic storm are discussed in Huang et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We attempt to quantify the importance of multiscale FACs with respect to their difference from the current large‐scale understanding and, therefore, choose large‐scale FACs as the baseline (i.e., the R1/R2 system). To define these FACs, we use the fitting method developed by Clausen et al () to derive R1/R2 FACs from AMPERE data and subsequently used prolifically to study the characteristics of large‐scale FACs (Carter et al, ; Coxon et al, , , ; Milan et al, ). We believe the R1/R2 FACs produced from the Clausen et al () method (hereafter C2012) more faithfully represent the distributions than empirical approaches such as Weimar (, ) because they are driven by instantaneous observations (shortcomings of the Weimer, , empirical model for dynamic representation during a geomagnetic storm are discussed in Huang et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Different choices of the background state will inevitably produce different results, and the choice should be driven by the objectives of the analysis. Because we are attempting to determine differences between multiscale FACs, we have chosen a data‐driven fit to large‐scale R1/R2 FACs (Clausen et al, ) that has been used prolifically in the FAC literature to study the characteristics of large‐scale FACs (Carter et al, ; Coxon et al, , , ; Milan et al, ). This choice represents perhaps our best ability to model the R1/R2 currents on an instantaneous basis and, therefore, ideally serves the objectives of this study. We have primarily investigated statistical results for multiscale FACs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One approach to the analysis of FAC observations from AMPERE has been the application of principal component analysis (PCA), which provides a means of decomposing the polar patterns of FACs into their dominant modes of variation (Cousins et al, ; Milan et al, , ). For instance, Cousins et al () and Milan et al () demonstrated that the region 1 and region 2 current systems (R1/R2) first identified by Iijima and Potemra (, ) are indeed the dominant component of the polar FACs and that the region 0 (R0) cusp current system (Iijima & Potemra, ; Iijima et al, ) is the second most important component. These studies also confirmed that the magnitude of the R1/R2 current patterns is controlled by the strength of the Dungey cycle flow in the magnetosphere (Dungey, ), related to the sense of the IMF B Z component, whereas the polarity of the R0 currents reflects the dawn‐dusk orientation of the IMF, that is, its B Y component (Iijima et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The Region 1 and Region 2 currents are also moderately correlated with both dayside reconnection and geomagnetic activity (Coxon et al, ). Interestingly, the substorm current wedge does not appear as a principal component of the FACs (Milan et al, ), although it can be revealed through differencing techniques (Clausen et al, ). While the large‐scale currents increase after substorm onset, AMPERE has also revealed that FACs decrease in a localized region close to the onset latitude and magnetic local time (MLT) just prior to onset, in keeping with the phenomenon of auroral dimming (Coxon et al, ; Murphy et al, ).…”
Section: Introductionmentioning
confidence: 99%